The Application of Learning Media " Tree Chart" to Improve Student Learning Outcomes for Tarikh Islam Lesson class 3 at Darussalam Modern Islamic Boarding School Gontor Ponorogo - Anwar, Heru Saiful; Zuhrotul Mufidah; Arrouf, Mustabshirin; Al-Murtadho, Ajib (EDUCAN : JURNAL PENDIDIKAN ISLAM, 2024)
One of the subject matter contained in Islamic education is Tarikh Islam lessons. Tarikh Islam are one of the required lessons for students to be taught at Darussalam Modern Islamic Boarding School, which is lesson learns about Islamic history including the story of Rasulullah, Khulafaur Rashidin, Companions of Rasulullah and others. In teaching and learning activities, media is one of the important factors in learning. In view of the scores obtained by grade 3 H students in Islamic date lessons, there are 20 out of 37 students or 53% of students who get scores below the passing score standard, it is due to the lack of teachers in providing innovation in learning activities so that students become bored and do not pay attention to the lessons taught. And one of the innovations that can be used is with (Tree Chart) media learning. This study aims to, improve student activeness and learning outcomes in Islamic date subjects Class 3 H at at Darussalam Modern Islamic Boarding School by using Tree Chart learning media. This type of research is Classroom Action Research. In this study, researchers as teaching teachers and assisted by an Observer who supervises the condition of students. This research consists of the first cycle and the second cycle which consists of: Planning, Implementation, Observation, and Reflection. Data collection techniques and tools in this study are using descriptive analysis techniques on data in the form of documentation of student learning outcomes, observation sheets and test results The results of this study show that (1) the application of tree chart learning media can increase student activity. With the presentation value of student activeness in the first cycle which reached 61.37% and increased in the second cycle which reached 84.12% with the presntase there was a difference between the first and second cycles which reached 22.75%. (2) The application of tree chart learning media can improve student learning outcomes. The percentage in the first cycle of students who completed learning was 22 students out of 37 students or reached 59.45% with an average score of 5.91 and in the second cycle as many as 37 students or reached 100% with an average score of 7.78. With the explanation above, it can be concluded that tree chart learning media can increase student activeness and learning outcomes. Keywords: Student Activeness, Learning Outcomes, Tarikh Islam Lessons, Tree Chart Learning Media